Workplace xenophobia, change resistance, and the new normal: implications for employee performance and inclusion - Anwar, Rana Salman; Androniceanu, Armenia; Grgurevic, Niksa; Ahmed, Rizwan Raheem; Parmar, Vishnu; Nasir, Fouzia (Transformations In Business & Economics, 2026)
This research examines workplace pandemic xenophobia and resistance to change. Second, the study examines how resistance to change affects eco-xenophobia under the influence of pandemic xenophobia. Third, the study examines how eco-xenophobia affects employee vaccine acceptability. Finally, the study examined how acceptance of vaccination affects cross-cultural workplace performance. The study found five variables: contextual performance, change resistance, pandemic xenophobia, eco-xenophobia, and vaccination acceptance. The researchers obtained 219 responses after merging the 156 Pakistani and 63 Chinese responses. This research presents thermographic data for citizens of both nations separately. This study employed SEM-PLS using Smart-PLS version 4.0 to assess the reliability, validity, and relevance of the structural model. The study's findings revealed that all hypotheses were approved. The findings demonstrate that resistance to change can lead to xenophobic attitudes in the workplace, which can hurt employee performance. The research also emphasizes the importance of addressing workplace xenophobia, which can significantly impact workplace dynamics and employee outcomes. The study advances the understanding of the relationship between resistance to change and xenophobic attitudes. This study posits that resistance to change is a precursor to xenophobic attitudes. The findings have implications for managers and organizations operating in multicultural settings, underscoring the need for proactive measures to combat xenophobia and promote diversity and inclusion in the workplace.
Keywords: Resistance to Change; Workplace Pandemic Xenophobia; Eco-Xenophobia; Workplace Performance; Employee Outcomes